Evaluation of Hospital Referral Notes for Pulmonary Function Tests at Tertiary Care Teaching Hospital in Oman - Al Hinai, Ruqaia (Oman Med J, 2020)
OBJECTIVES: There is substantial increase in referrals for investigations at Sultan Qaboos University Hospital (SQUH). Evaluating the quality of hospital referral notes (RNs) is necessary from diagnostic, patient, and economic perspectives. RNs for pulmonary function tests (PFTs) can be considered as representative of the array of tests performed at SQUH. METHODS: This cross-sectional study evaluated the quality of RNs based on ‘completeness’ for all consecutive patients referred for PFTs at SQUH over six months. Evaluation included documentation of demographic features, RNs date, priority for investigation, referral reason, pulmonary and relevant medical and smoking history for spirometry RNs, and addition of hemoglobin level for full lung functions (Full-LuFs) tests. The proportion of complete RNs was determined and analyzed separately to study association of spirometry and full-LuFs tests with source and reasons for referral. RESULTS: Only 644 of 683 RNs were available for analysis. Smoking history was stated in only 3.3% of all RNs; hence, it was excluded from the analysis. RNs were complete only in 12.4% of cases for spirometry and 14.4% for full-LuFs tests. RNs for patients who primarily had pulmonary disease were proportionately incomplete than those for patients with other reasons (p < 0.050). There was no significant association between incompleteness of RNs and referral hospital (SQUH vs. non-SQUH) and SQUH inpatient or outpatient status implying that the overall proportion of completeness of RNs from all concerned referral locations was similar and low in both types of RNs. CONCLUSIONS: There is a need to improve the quality of RNs at SQUH. Referring doctors must be made aware of the importance of completeness of RNs to improve test reporting, patient management and satisfaction, and reduce financial burden on hospital exchequer.